Student’s Ability of Identifying Elements of Poetry Through Group Discussion: Array - Husda, Azizah (Universitas Harapan Medan, 2021)
This research was on the study of English literature. The objectives were firstly to investigate students’ ability of English Department, Teaching Training and Education at Prima Indonesia University, then to find out elements of poetry. This research applied descriptive qualitative approach with group discussion method and a case study design where one class at fourth semester was taken as the subjects. The instrument used in this research was an essay test taken from one of Robert Frost’s poems. Through group discussion, the students worked cooperatively to analyze the poems by sharing their arguments and ideas as the requirements to accomplish the study of poetry. The data source was the scores that led to find the criteria of the students’ ability. Based on the findings, the elements of poetry identified were stanza, lines, rhyme, rhyme scheme, rhythm, syllables, meter, foot, mood, tone, imagery, and figure of speech. Then, there were 80% students able to identify the elements of poetry. While 20% remaining were the unable students. In conclusion, there were three of four groups assigned, classified able to identify the elements of poetry. It is suggested that group discussion is one of significant cooperative learning strategy in any instructional process.